Proceso de atención de enfermería en paciente adulto mayor con diagnóstico de leucemia linfoblástica. - Moreira Fuentes, Eilin Gisselle (2023)
The development of this clinical case was based on the nursing care process in an older adult patient diagnosed with lymphoblastic leukemia, in which the general objective was to apply the nursing care process in an older adult patient diagnosed with lymphoblastic leukemia. It is important to point out that leukemia is known as a type of cancer that affects blood cells, specifically leukocytes, and is characterized by an inadequate production of these malignant cells in the bone marrow, which leads to the reduction of other normal blood cells. Based on the results, in the development of this clinical case, the clinical complexity of the patient was evidenced where severe symptoms such as fever, disorientation, unconsciousness are linked, where it suggests a medical and dangerous condition. The presence of cancer in the patient is an additional process in terms of the complexity of the case. In conclusion, it was possible to apply the nursing care process effectively in the case of this adult patient with the diagnosis of lymphoblastic leukemia, relevant assessments were performed where altered function patterns were identified, and nursing interventions were performed to meet the patient's needs.